Improving Indonesian Language Learning Outcomes Through Interactive Learning Models (Explicit Introduction) In Class V Students of SD Negeri 3 Barru - Anih, Anih; Munandar, Faishal; Nadrah, Nadrah (Lembaga Penelitian dan Pendidikan Mandala, 2025)
This research aims to determine the improvement in indonesian language learning outcomes through an interactive learning model (Explicit Introduction) in class V UPTD SD Negeri 3 Barru, Siawung Village, District. Barru. With this research, the researcher used the classroom action research (PTK) method, namely research carried out in the classroom as an effort to examine, analyze and critically analyze the teacher's learning plan, the teacher's interaction with students, and how students interact in class. Data collection was carried out using text from student learning results and non-text in the form of observations of scientific implementation. Research in cycle I, namely of the 20 students who succeeded in reaching the KKM, only 5 students, after carrying out cycle II, 18 students experienced an increase. The conclusion of this research is that the scientific approach is able to improve student learning outcomes in learning Indonesian through interactive models (Explicit Introduction).